2000
DOI: 10.1042/cs0990037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperglycaemia and hyperinsulinaemia on proximal gastric motor and sensory function in humans

Abstract: A B S T R A C TDuring acute hyperglycaemia, gastric emptying is delayed and the compliance of the proximal stomach is increased significantly. It is not known whether the effect of hyperglycaemia on proximal gastric motor function in healthy volunteers results from endogenous hyperinsulinaemia. Therefore we studied the effects of acute hyperglycaemia and hyperinsulinaemia on proximal gastric function, measured using an electronic barostat. Eight healthy volunteers were studied on three separate occasions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similarly, hyperglycemia has been shown to be associated with diminution in pulmonary function, even in nondiabetic adults (10). Hyperglycemia also results in delayed gastric emptying and decreased small intestinal motility in adults (11,12). Other studies have demonstrated the association of hyperglycemia with infections both in adults and children (13)(14)(15).…”
mentioning
confidence: 95%
“…Similarly, hyperglycemia has been shown to be associated with diminution in pulmonary function, even in nondiabetic adults (10). Hyperglycemia also results in delayed gastric emptying and decreased small intestinal motility in adults (11,12). Other studies have demonstrated the association of hyperglycemia with infections both in adults and children (13)(14)(15).…”
mentioning
confidence: 95%
“…A number of studies have demonstrated that even a short-term increase in serum glucose has a direct inhibitory action on gastric emptying in healthy adults as well as diabetic patients. [29][30][31] The acute effects of severe hyperglycemia on gastric emptying is a distinct entity and generally less well known than that of diabetic gastroparesis. The delay in gastric emptying related to severe hyperglycemia occurs quickly but is reversible with good glucose control, which is in contrast to the more insidious onset and intractability of diabetic gastroparesis.…”
Section: Gastric Emptyingmentioning
confidence: 99%
“…Even in non-diabetic people, hyperglycemia has been linked to decreased lung function and death from gunshot wounds to the brains in children 21 . Adults with hyperglycemia also experience prolonged stomach emptying and reduced small intestine motility 22,23 . Other investigations have shown that infections can occur in both adults and children who have hyperglycemia [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%